Changes in and Modelling of Hydrological Process for a Semi-Arid Catchment in the Context of Human Disturbance - Liu, Yue; Zhang, Jianyun; Yang, Qinli; Zhou, Xiong; Wang, Guoqing (Frontiers in Earth Science, 2021)
Effective and accurate hydrological modelling in semi-arid catchments is of great significance to water resources management and assessment. However, intensive and complex human activities are changing the elements of hydrological cycle process, restricting further development and application of hydrological models. This study focuses on the Zhulong River catchment, one of the main grain producing areas in northern China, situated in the semi-arid climate zone, and examines hydrological processes during the natural period (1967-1979), moderate human impact period (1980-1996) and intensive human impact period (1997-2015). The results show that (1) the annual precipitation and temperature of the catchment both presented upward trends, while the annual observed runoff exhibited a significant downward trend, with the influence of human activities the main cause for runoff reduction in this catchment; (2) the correlations between runoff and precipitation were comparatively high both on monthly and annual scales during the natural period until the impacts of human activities intensified; (3) the runoff in the natural period was mainly concentrated in July to October, and maximum seasonal runoff during the moderate human impact period appeared in August, with the flow almost running dry during the intensive human impact period; (4) the daily discharge process in a same precipitation situation decreased significantly in human impact periods, but the interval time between flood peaks and rainfall peaks was shortened; (5) the GR4J model performed well for runoff simulations in the Zhulong River catchment during the natural period but gradually lost its applicability with the intensification of human activities; (6) the changes of underlying surface and construction of water conservancy projects reduced the streamflow and complicated the regional water cycle process, with water resources consumption for industrial and agricultural production the primary factor aggravating water shortages in the Zhulong River catchment.